2018
DOI: 10.1186/s13071-018-2751-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a duplex real-time PCR assay for the diagnosis of equine piroplasmosis

Abstract: BackgroundEquine piroplasmosis (EP) is an economically significant infection of horses and other equine species caused by the tick-borne protozoa Theileria equi and Babesia caballi. The long-term carrier state in infected animals makes importation of such subclinical cases a major risk factor for the introduction of EP into non-enzootic areas. Regulatory testing for EP relies on screening of equines by serological methods. The definitive diagnosis of EP infection in individual animals will benefit from the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…Equine piroplasmosis has been previously reported in Iraq using several direct and indirect methods that detected B. caballi and T. equi including Giemsa stained blood smears (Alssad, 2009), cELISA (Alsaad and Al-Obaidi, 2012; Aziz and Al-Barwary, 2019). However these methods are suitable only for the detection in the acute stage of infection, but they are not applicable in identifying presymptomatic and carrier animals with low parasetemia (Lobanov et al, 2018). Therefore, this study aimed to investigate the frequency rate of piroplasms infection in different species of equids from Erbil province, North Iraq by molecular technique and to document the phylogenic sequencing of PCR products for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Equine piroplasmosis has been previously reported in Iraq using several direct and indirect methods that detected B. caballi and T. equi including Giemsa stained blood smears (Alssad, 2009), cELISA (Alsaad and Al-Obaidi, 2012; Aziz and Al-Barwary, 2019). However these methods are suitable only for the detection in the acute stage of infection, but they are not applicable in identifying presymptomatic and carrier animals with low parasetemia (Lobanov et al, 2018). Therefore, this study aimed to investigate the frequency rate of piroplasms infection in different species of equids from Erbil province, North Iraq by molecular technique and to document the phylogenic sequencing of PCR products for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, these methods are more often used for research than in clinical practice [2,3,5,20,68,[85][86][87][88][89][90][91][92]. Numerous assays targeting one or multiple EP parasites, including conventional PCR [86,87], nested PCR (nPCR) [90,93], real-time PCR (rtPCR) [82,[94][95][96][97][98][99], multiplex PCR (mPCR) [87,89], reverse line blot (RLB) [100,101], and loop mediated isothermal amplification (LAMP) [85,88,91], have been developed. Several of these assays were determined to have high sensitivity, with a detection limit of 10 −7 % parasitized erythrocytes (PE) [2,3,5,20,68,[85][86][87][88][89][90][91][92].…”
Section: Diagnosismentioning
confidence: 99%
“…Several of these assays were determined to have high sensitivity, with a detection limit of 10 −7 % parasitized erythrocytes (PE) [2,3,5,20,68,[85][86][87][88][89][90][91][92]. Quantitative methods, such as rtPCR (qPCR), have also been developed, but are mostly applied to increase the sensitivity of parasite detection, and are rarely used to evaluate parasite loads [94][95][96][97][98][99]102].…”
Section: Diagnosismentioning
confidence: 99%
“…Real-time PCR is the widely-recognized gold standard of genomic DNA identification and quantification due to its good specificity and high sensitivity. In this study, we employed the reported PCR primers and probes to assay pUC57-Bc18S and pUC57-ema DNA 26,28 and the results showed that 2.0 fg pUC57-Bc18S DNA (Figs. 4e) and 2.0 fg of pUC57-ema DNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a comparison, real-time PCR assay was also performed. Primers and probes reported in a previous duplex qPCR assay of EP 26,28 (Table 4) were synthesized by Sangon Biotech (Shanghai, China). The PCR reactions were run on a Light Cycler 480 (Roche, USA) using a TaqMan Gene Expression Master Mix (Thermo Fisher Scientific, USA).…”
Section: Construction Of Recombinant Plasmid Carrying Targeting Genesmentioning
confidence: 99%